2019
DOI: 10.3390/geosciences9060270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Pooling Methods to Establish a Multi-Century δ18O Chronology for Paleoclimate Reconstruction

Abstract: To develop multi-century stable isotope chronologies from tree rings, pooling techniques are applied to reduce laboratory costs and time. However, pooling of wood samples from different trees may have adverse effects on the signal amplitude in the final isotope chronology. We tested different pooling approaches to identify the method that is most cost-efficient, without compromising the ability of the final chronology to reflect long-term climate variability as well as climatic extreme years. As test material,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(135 reference statements)
0
7
0
Order By: Relevance
“…As the distance between their foliar system and the soil increases, trees leave an atmosphere containing respired 13 C-depleted CO 2 . They also progressively access the open atmosphere, where CO 2 is 13 C-rich, generating a positive trend in the cellulose δ 13 C with time (Francey and Farquhar, 1982;Schleser and Jayasekera, 1985). In open canopies, the ambient conditions as trees get taller are relatively stable, and the isotopic effects described above are very likely limited to non-existent (Brienen et al, 2017;Klesse et al, 2018).…”
Section: Height and Stand Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the distance between their foliar system and the soil increases, trees leave an atmosphere containing respired 13 C-depleted CO 2 . They also progressively access the open atmosphere, where CO 2 is 13 C-rich, generating a positive trend in the cellulose δ 13 C with time (Francey and Farquhar, 1982;Schleser and Jayasekera, 1985). In open canopies, the ambient conditions as trees get taller are relatively stable, and the isotopic effects described above are very likely limited to non-existent (Brienen et al, 2017;Klesse et al, 2018).…”
Section: Height and Stand Dynamicsmentioning
confidence: 99%
“…Over the last decade, the awareness of this effect on δ 13 C series has spread widely, and most scientists reconstructing climatic parameters using δ 13 C values opt to correct these ratios to minimize biased δ 13 C-climate correlations (e.g., Andreu-Hayles et al, 2017). Several methods to obtain pre-industrial tree-ring δ 13 C series apply proportional corrections to rising pCO 2 ranging between 0.0073 and 0.02 ‰ ppm −1 (Feng and Epstein, 1995;Kürschner, 1996;Saurer et al, 2003;Konter et al, 2014). The performance of the proportional correction may improve by testing the reproduction of instrumental climatic series and adapting a corrective factor specific to the investigated region (Treydte et al, 2009).…”
Section: Physiological Effects Of Rising Pcomentioning
confidence: 99%
“… Loader et al, 2008 ; Rinne et al, 2013 ; Robertson et al, 1997 ; Young et al, 2012a , 2015 ). Such an enormous age-trend would certainly compromise any environmental signals, including the independently-determined δ 13 C ‘Suess effect’ and the pooling of wood samples prior to chronology construction ( Borella et al, 1998 ; Dorada-Liñan et al, 2011 ; Foroozan et al, 2019 ; Leavitt, 2008 ; Liu et al, 2015 ; Szymczak et al, 2012 ) would not be justified. We seek to test the predictions of Brienen et al (2017) using annually-resolved stable carbon isotope time-series from UK oak timbers and trees.…”
Section: Introductionmentioning
confidence: 99%
“…Since the extremely narrow tree rings of junipers pose an analytical challenge to provide sufficient material for isotope analyses, equal wood masses of five individuals of exactly dated trees (1957-1515) were pooled prior to isotopic analysis and further processed for α-cellulose extraction. In previous methodological studies evaluating the common signal between individual isotope series from juniper trees [29] and the suitability of different pooling methods, we demonstrated that this number of trees and the approach of inter-tree pooling is the best alternative to individual-tree isotope measurements [59]. Inter-tree pooling enables the establishment of a reliable regional δ 18 O isotope chronology providing a representative climate signal for the region.…”
Section: Development Of the Stable Oxygen Isotope Chronologymentioning
confidence: 91%